Role of B-Cell Lymphoma/Leukemia 11A in Normal and Malignant Hematopoiesis - Haihang Zhang; Junhao Zeng; Fangling Zhang; Jing Liu; Long Liang (Biology)
B-cell lymphoma/leukemia 11A (BCL11A) is a crucial transcriptional regulator, widely recognized for its role in controlling fetal hemoglobin and its potential as a gene therapy target for inherited hemoglobinopathies. Beyond this, recent studies have also highlighted its key role in the maturation and function of immune cells and erythrocytes, mediated through the regulation of various molecules during hematopoietic development. The dysregulation of BCL11A disrupts downstream molecular pathways, contributing to the development of several hematological malignancies, particularly leukemias. This review provides a comprehensive overview of the role of BCL11A in normal and malignant hematopoiesis, details the hematological disorders associated with its dysregulation and explores the current therapeutic strategies targeting this transcription factor.